2006
DOI: 10.1111/j.1467-9620.2006.00700.x
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Exploration of the Who, What, and how of School Care

Abstract: This study examines how care exists in one alternative high school for students at risk of dropping out. Specifically, this article empirically explores who is involved in caring relationships at the school, what those relationships look like, and how the organization of the school affects the existence of care. Data were collected during the 2000–2001 school year and included observations, faculty interviews, and in-depth interviews with 16 students. From these data, a construct of care was created that inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
5

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 33 publications
0
23
0
5
Order By: Relevance
“…What is known currently about the topics of values, ethics, and moral leadership in the field of educational leadership pertains to how practicing educational leaders approach, or should approach, decision making and their consequent actions along various ethical frameworks, that is, justice, care, critique, community, administrative virtue, and other moral vantage points (Schussler and Collins 2006;Starratt 1991).…”
mentioning
confidence: 99%
“…What is known currently about the topics of values, ethics, and moral leadership in the field of educational leadership pertains to how practicing educational leaders approach, or should approach, decision making and their consequent actions along various ethical frameworks, that is, justice, care, critique, community, administrative virtue, and other moral vantage points (Schussler and Collins 2006;Starratt 1991).…”
mentioning
confidence: 99%
“…Both Schussler and Collins (2006) and Cassidy and Bates (2005) found that caring was embedded into the culture of the alternative high schools studied by both pairs of researchers. Schussler and Collins stated that structures such as school and class size and the core school value of caring "created opportunities for individuals…to act in caring ways" (p. 1484).…”
Section: Further Research On Caring School Communitiesmentioning
confidence: 99%
“…Rather than give the details of each study due to the similarity of methods, the results have been categorized into three categories: (a) personal, (b) socialemotional, and (c) academic (Schussler & Collins, 2006).…”
Section: How Teachers Demonstrate Care For Studentsmentioning
confidence: 99%
See 2 more Smart Citations